Drug repositioning meets precision in glioblastoma - Wick, Wolfgang; Keßler, Tobias (Clinical cancer research, 2018)
Glioblastoma has a gigantic unmet medical need. Molecular knowledge has evolved substantially, including data on clonal selection with progression. Past trials for all-comers may have produced false negative results. Molecular precision at progression needs workup of new tissue, and revisiting drugs with a focus on brain tumor penetration may yield surprises. Clin Cancer Res; 24(2); 256-8. ©2017 AACR. See related article by Byron et al., p. 295
Gesehen am 23.04.2018